Influence of the trapeziometacarpal joint fusion on thumb muscles and thumb-tip movement: A cadaveric study. (July 2019) - Kawano, Y.; Nakamura, T.; Tada, M.; Nagura, T.; Matsumoto, M.; Nakamura, M.; Sato, K.
Abstract: Background: Trapeziometacarpal (TMC) arthrodesis provides stability and strength of the thumb, whereas fixation of the TMC joint restricts motion of the thumb, which may consequently impair the activity of daily living. The objective of our study was to investigate how length and area of the thumb-tip trajectory were reduced after the TMC joint fusion. Methods: Six fresh, frozen cadavers were used for this study. Tension was applied to the distal tendons of 4 extrinsic thumb muscles (extensor pollicis longus, flexor pollicis longus, abductor pollicis longus, and extensor pollicis brevis) by servomotor, whereas tension was applied to 4 intrinsic muscles (abductor pollicis brevis, opponens pollicis, flexor pollicis brevis, and adductor pollicis) using static weights. The thumb-tip trajectory was examined using a motion capture system without tension and with 5 different weights to induce intrinsic muscle tension before and after the TMC joint fusion. Findings: When tension was applied to the intrinsic muscles, the length of the thumb-tip trajectory decreased in all conditions compared with that before the TMC joint fusion, whereas the trajectory decreased only when the abductor pollicis longus was pulled. The overall thumb-tip trajectory area was reduced to approximately 30% compared with that before the TMC joint fusion. Interpretation: Thumb-tip trajectory was restricted by the TMC joint fusion to approximately 30%. However, the reduced area was found tolerable for performing daily activities. Thus, arthrodesis can be the first-line treatment in patients who wish to engage in activities of daily living without difficulties. Highlights: We investigated the influence of the trapetiometacarpal joint fusion. The trapeziometacarpal joint fusion affected all intrinsic muscles of the thumb examined. For extrinsic muscles trapeziometacarpal joint fusion only affected abductor pollicis longus. Thumb-tip trajectory area was reduced to approximately 30% before trapeziometacarpal joint fusion. The reduced area was mostly found in a tolerable area in activity of daily living.